2012
DOI: 10.1159/000345550
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc Intake and Kidney Stone Formation: Evaluation of NHANES III

Abstract: Aims: We aimed to determine whether there is an association between dietary zinc intake (DZI) and prevalent kidney stone disease defined as self-report of any previous episode of kidney stone. Methods: We examined The Third National Health and Nutrition Examination Survey (NHANES III), a large US population-based cross-sectional study, and used logistic regression analyses to determine the independent association between DZI and prevalent kidney stone disease. Results: A total of 15,444 men and women over 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Strontium, cadmium, and zinc are trace elements and have been associated with USD in laboratory and epidemiologic studies (39,40). Additionally, calcium oxalate stones have been found to contain zinc and strontium (39).…”
Section: Environmental Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Strontium, cadmium, and zinc are trace elements and have been associated with USD in laboratory and epidemiologic studies (39,40). Additionally, calcium oxalate stones have been found to contain zinc and strontium (39).…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Vitamin D supplementation, conversely, has not been associated with stones (52), perhaps because its conversion to 1,25-dihydroxyvitamin D is limited by activity of 1-a-hydroxylase. An association between high dietary zinc intake and an increased odds of USD has been observed (40).…”
Section: Dietmentioning
confidence: 99%
“…Two studies using data from the Third National Health and Nutrition Examination Survey (NHANES III) and the European Prospective Investigation into Cancer and Nutrition (EPIC) reported an association between high dietary zinc intake and increased risk of urinary stones. 78,79 However, attempts to assess zinc status in individual patients have resulted in conflicting information. Data from a report published in 1963 and one publication from 2007 showed that calcium-based stone formers had lower urinary zinc levels compared with controls, consistent with an inhibitory effect of zinc on calcium-based stone formation.…”
Section: The Elementome Of Urinary Stonesmentioning
confidence: 99%
“…9 We increased planned enrollment to 60 participants because prior studies of zinc and kidney stone disease did not include dietary phytate in the analyses. Because phytate binds zinc in the gut and also may directly inhibit stone formation, we anticipated that more patients would be needed to detect an association between zinc and kidney stones after adjusting for phytate.…”
Section: Methodsmentioning
confidence: 99%
“…In a study using the National Health and Nutrition Examination Survey (NHANES), dietary zinc intake was higher among older adults with nephrolithiasis, but lower among younger adults with nephrolithiasis. 9 Earlier studies examining urinary zinc levels in adults with and without nephrolithiasis also reported disparate results. 10, 11 These prior studies were cross-sectional, included only adults, and were likely confounded by unmeasured dietary intakes such as phytate, which binds zinc in the gut and decreases its bioavailability.…”
Section: Introductionmentioning
confidence: 99%